(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2015)
Posterior edentulous area and implant supported restorations are two important aspects in dentistry. Posterior edentulous area can’t be restored effectively with partial denture or conventional bridge work The replacement of missing teeth with implant borne restorations in such conditions is gaining increasing popularity day by day. This case report describes the successful management of a posterior edentulous area using Bicon implant. The result was good, which further validate the use of this technique for suitable patient management. JCMCTA 2015 ; 26 (1) : 63-65